Semantic keyword-based search on structured data sources : COST Action IC1302 second International KEYSTONE Conference, IKC 2016, Cluj-Napoca, Romania, September 8-9, 2016, Revised selected papers /: COST Action IC1302 second International KEYSTONE Conference, IKC 2016, Cluj-Napoca, Romania, September 8-9, 2016, Revised selected papers. (2017) - Unknown
No abstract available